2020
DOI: 10.1155/2020/7315253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin as an Antioxidant Drug to Reverse Hepatic Steatosis: Experimental Model

Abstract: Introduction. The hepatic steatosis of the nonalcoholic origin or NAFLD is increasing at present, particularly in Western countries, parallel to the increase in obesity, constituting one of the most prevalent hepatic processes in the Western society. Melatonin has been successfully tested in experimental models in mice as a drug capable of reversing steatosis. The effect of melatonin on fat metabolism can be summarized as a decrease in lipid peroxidation and a decrease in oxidative stress, biochemical phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The availability of a large animal model of NAFLD with initial NASH in a short period may be of particular interest to understand the onset of NAFLD and its progression to NASH, to explore new treatments for this ailment 41 and to better characterize the steatotic liver for transplant procedures 36 . In these two experiments, 20 animals were provided the steatotic diet and all of them reached NAFLD according FLIP algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of a large animal model of NAFLD with initial NASH in a short period may be of particular interest to understand the onset of NAFLD and its progression to NASH, to explore new treatments for this ailment 41 and to better characterize the steatotic liver for transplant procedures 36 . In these two experiments, 20 animals were provided the steatotic diet and all of them reached NAFLD according FLIP algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, melatonin were used as treatment of NAFLD, previous reports illustrated that melatonin therapy decreased the severity of steatosis, inhibited the immigration of inflammatory cells, protected hepatic cells from damage, and also reduced serum and tissue inflammatory cytokines concentration. 25 - 27 …”
Section: Discussionmentioning
confidence: 99%
“… 14 , 28 It is noteworthy that melatonin administration exhibited distinct improvements on histology in diet-induced NAFLD mice or pigs. 29 , 30 There are barely any studies on db/db diabetic mice that verify the therapeutic action of melatonin for NAFLD. In this study, we found that melatonin slightly reduced blood glucose and ameliorated dyslipidemia, hepatic enzymes, and MMP.…”
Section: Discussionmentioning
confidence: 99%